Indicadores de delimitação do leito maior sazonal na gestão de áreas protegidas: uma revisão de escopo - Camilo, Daniel Salvaia (Universidade Federal de São Carlos, 2026)
Seasonally inundated environments perform essential ecological functions for biodiversity conservation, flood mitigation, and hydrogeomorphological stability. In this context, the seasonal high-water channel constitutes an important technical reference for the protective delineation of riparian ecosystems. Despite its relevance, legal reforms have replaced this parameter with simplified geometric criteria due, among other factors, to claims regarding the impracticability of objectively delineating such areas. This study aimed to map the methods, indicators, and concepts employed in the delineation of seasonally inundated areas and to analyze their implications for environmental management and land-use planning. A scoping review was conducted following the PRISMA-ScR protocol, combining searches across five scientific databases with reference and citation tracking strategies, resulting in a total of 46 analyzed studies. The findings demonstrated that substantial terminological dispersion hinders both the understanding and protection of these environments and enabled the organization of the identified methods into three methodological groups according to their predominant mode of accessing the inundation phenomenon: hydrogeomorphological approaches, which interpret persistent physical and biological evidence preserved in the landscape; multitemporal remote sensing, which empirically records the occurrence and spatial extent of flooding over time; and hydraulic modeling, which projects potential scenarios under different hydrological conditions. This classification demonstrates that each group captures a complementary dimension of the phenomenon, highlighting that methodological integration through the convergence of multiple lines of evidence enhances the technical consistency of delineation processes and strengthens environmental decision-making in protected areas, while also providing technical support for the application of the in dubio pro natura principle under conditions of uncertainty. Based on these findings, a technical product was developed consisting of a proposed technical resolution and an operational protocol structured into progressive levels of analysis, intended to support environmental licensing, enforcement, and territorial planning procedures, with emphasis on methodological integration, traceability of technical decisions, context-sensitive application, and explicit documentation of uncertainties.
Indicators for delineating the seasonal high water mark in the management of protected areas: a scoping review
Keywords: Planícies aluviais; Zonas ripárias; Áreas úmidas; Dinâmica hidrológica; Planejamento territorial; Floodplains; Riparian systems; Wetlands; Hydrological dynamics; Land-use planning; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::HIDROLOGIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL; 6. Água Potável e Saneamento; 11. Cidades e Comunidades Sustentáveis; 13. Ação contra a Mudança Global do Clima; 15. Vida Terrestre